Microwave-Hydrothermal Rapid Synthesis of Cellulose/Ag Nanocomposites and Their Antibacterial Activity - Fu, Lian-Hua (Nanomaterials (Basel), 2018)
Silver-based antimicrobial nanomaterials are considered as the most promising antibacterial agents owing to their outstanding antimicrobial efficacy and their relatively low toxicity to human beings. In this work, we report on a facile and environment-friendly microwave-hydrothermal method to prepare cellulose/Ag nanocomposites using hemicellulose as the reductant. The influences of the microwave-hydrothermal heating time and temperature, as well as the hemicellulose concentration on the formation of cellulose nanocomposites, were investigated in detail. Experimental results indicated that the hemicellulose was an effective reductant for silver ions, with higher temperature and longer heating time favoring the formation of silver with higher crystallinity and mass content in the nanocomposites. Moreover, the antimicrobial properties of the as-prepared cellulose/Ag nanocomposites were explored using Gram-positive S. aureus ATCC 6538 and Gram-negative E. coli HB 101 by both disc diffusion method and agar dilution method, and the nanocomposites showed excellent antibacterial activity. These results demonstrate that the as-prepared cellulose/Ag nanocomposites, as a kind of antibacterial material, are promising for applications in a wide range of biomedical fields.